Răspuns:
Explicație pas cu pas:
a)
=2/3+1/6⁽³*3⁽³/4
=⁸⁾2/3+³⁾1/8
=16/24+3/24
= 19/24
-
b)
= 13/6-5⁽⁵/9⁽⁹*27⁽⁹/25⁽⁵
=⁵⁾13/6-⁶⁾3/5
=65/30-18/30=47/30
-
c)
=3+5⁽⁵/4*9/5⁽⁵
= ⁴⁾3+9/4
=12/4+9/4=21/4
-
d)
=23/2-4⁽⁴*9/4⁽⁴
= 23/2- ²⁾9
=23/2-18/2= 5/2
-
e)
= 2⁽²/3⁽³*9⁽³/8⁽²+5⁽⁵/4⁽⁴*8⁽⁴/15⁽⁵
=³⁾3/4+⁴⁾2/3
=9/12+8/12
=17/12
-
f)
= 7-9/4⁽²*2⁽²
= ²⁾7- 9/2
=14/2-9/2=
=5/2
-
g)
=7/6+1/10 *( ²⁾4/3-³⁾1/2)
= 7/6+1/10*( 8/6-3/6)
= 7/6+1/10⁽⁵ *5⁽⁵/6
=²⁾7/6+1/12
=14/12+1/12=
=15⁽³/12⁽³
=5/4
-
h)
3-4/3*(1/6+1/9⁽³*3⁽³/4)
= 3-4/3*( ⁶⁾1/6+1/36)
= 3-4/3*(6/36+1/36)
=3-4/3*7/36
=¹⁰⁸⁾3-28/108
= 324/108-28/108
=296⁽²/108⁽²
=148⁽²/54⁽²
=74/27